Transparent ceramic with high infrared-visible transmittance and preparation method thereof
By adopting a non-stoichiometric composition of MgAlxGa2O4+1.5x and optimizing the wet grinding process, the problem of pore accumulation during the sintering process of transparent ceramic materials is solved, and high visible-infrared transmittance and excellent mechanical properties are achieved.
Patent Information
- Application Number
- CN202411453944.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing transparent ceramic materials are prone to cause local pore aggregation during the sintering process, affecting optical quality, and have a narrow transmission domain in the infrared transmission band and insufficient high temperature stability.
It is composed of non -chemical measurement mgalxga2O4+1.5X. By optimizing the wet mill process and the introduction of dispersant, the powder particle size is refined, the pink uniformity and activity are improved, and the pores are eliminated during the sintering process.
Effectively improved the phenomenon of pores and improved optical uniformity. In the visible-infrared band, it showed a high pass rate and had good mechanical properties. The infrared cut-off edge broadcasted about 0.7-1.1 μm.
Smart Images

Figure CN119349992A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of transparent ceramics, and specifically relates to a transparent ceramic with high visible-infrared transmittance and a preparation method thereof. Background Art
[0002] Transparent armor, infrared windows, fairings and protective windows of aircraft require materials with high linear transmittance in the visible light band of 380-760nm and the mid-infrared band of 3-6μm. In addition, it is also required to have sufficiently excellent mechanical and thermal properties to resist the impact of foreign objects such as missiles, sand and gravel, air friction and high temperature. Transparent ceramic materials are considered to be ideal candidates for transparent armor, infrared windows, fairings and protective windows of aircraft.
[0003] In recent years, transparent ceramic materials such as AlON, MgF2, and MgAl2O4 have developed rapidly, and their preparation technologies are relatively mature. AlON transparent ceramics have excellent mechanical properties, comparable to sapphire, and low preparation costs, but the transmission area in the infrared transmission band is narrow, and the stability at high temperatures is not good enough. MgF2 transparent ceramics have a sufficiently wide optical transmission area, but relatively poor mechanical properties; MgAl2O4 transparent ceramics have relatively excellent comprehensive performance, but it is difficult to prepare high-transmittance samples, and often rely on sintering aids to improve optical quality, but to a certain extent affect mechanical properties and optical uniformity. Further development of new transparent ceramics to meet the needs of transparent armor, infrared windows, aircraft fairings and protective windows has become a technical problem that needs to be solved urgently.
[0004] Studies have shown that spinel-type Mg-Al-Ga-O solid solution can be quickly obtained by solid phase reaction of three oxides MgO-Al2O3-Ga2O3 at high temperature, and has a wide solid solubility range, which may be a potential transparent ceramic material. Patent CN 114773049A discloses a stoichiometric Mg(Al x Ga 1-x )2O4 transparent ceramic material, which has excellent optical quality in the visible-infrared band, can meet the material performance requirements of transparent armor, infrared windows, aircraft fairings and protective windows. Although this solution can meet the requirements of wide-band transmission from visible light to infrared band, it is easy to cause localized accumulation of pores during the sintering process (this problem is particularly obvious during the process of ceramic size enlargement), which in turn leads to white spots visible to the naked eye, affecting the optical quality of the sample. Summary of the invention
[0005] The main purpose of the present invention is to provide a spinel transparent ceramic with high visible-infrared transmittance, which has a wide light wave transmission range and high hardness, and can effectively improve the existing Mg (Al x Ga1-x ) It can solve the problems of local pore aggregation in 2O4-based transparent ceramics and narrow transmittance range of magnesium-aluminum spinel transparent ceramics; and the preparation process involved is simple, the raw materials are easy to obtain, the cost is low, and it is suitable for popularization and use.
[0006] To achieve the above object, the technical solution of the present invention is implemented as follows:
[0007] A transparent ceramic with high visible-infrared transmittance, wherein the chemical formula of the transparent ceramic is MgAl x Ga2O 4+1.5x , the value range of x is 0<x≤1.5.
[0008] Preferably, the value range of x is 0.8 to 1.2.
[0009] In the above scheme, the average grain size of the transparent ceramic is not higher than 50 μm, the size distribution is uniform and the range is not more than 10 μm, and there is no abnormal grain growth and local pore aggregation.
[0010] In the above scheme, under the same process conditions, compared with the stoichiometric Mg(Al x Ga 1-x )2O4-based transparent ceramics, the prepared samples have no obvious pore aggregation, and the optical uniformity is greatly improved; compared with magnesium aluminum spinel transparent ceramics, the infrared cutoff edge is widened by about 0.7 to 1.1 μm. The transparent ceramics have excellent optical and mechanical properties, high transmittance in the visible-infrared band, an optical transmittance range of 250 to 7500 nm, and a Vickers hardness of 12 to 13 GPa.
[0011] Preferably, the transparent ceramic material has a maximum transmittance of 82% in the visible light band of 400-800 nm, a maximum transmittance of 85% in the infrared band of 2.5-5.5 μm, and a Vickers hardness of 13 GPa.
[0012] The above MgAl x Ga2O 4+1.5x The method for preparing transparent ceramics comprises the following steps:
[0013] 1) Single-phase MgAl x Ga2O 4+1.5x Powder or chemical formula MgAl x Ga2O 4+1.5x Weighing a mixed powder of Mg, Al source and Ga source in a stoichiometric ratio as a raw material powder, mixing it with a ball milling medium and a dispersant, and then ball milling, drying, calcining, and sieving to obtain a target powder;
[0014] 2) pressing the powder obtained in step 1) into a shape and sintering to obtain a ceramic sintered body with a density greater than 99%;
[0015] 3) annealing the obtained ceramic sintered body in an oxidizing atmosphere, cooling, and polishing to obtain the transparent ceramic with high visible-infrared transmittance.
[0016] In the above scheme, the raw material powder can be MgAl x Ga2O 4+1.5x Powder or according to the chemical formula MgAl x Ga2O 4+1.5x , a mixed powder of Mg source, Al source and Ga source weighed in a stoichiometric ratio of 0<x≤1.5.
[0017] Furthermore, the purity of the Mg source, Al source and Ga source is above 99.9%; x Ga2O 4+1.5x The purity of the powder is greater than 99.9%.
[0018] Optionally, the Mg source is at least one of Mg-containing oxides, Mg-containing hydroxides, Mg-containing inorganic salts and their crystalline hydrates; the Al source is at least one of Al-containing oxides, Al-containing hydroxides, Al-containing inorganic salts and their crystalline hydrates; the Ga source is at least one of Ga-containing oxides, Ga-containing hydroxides, Ga-containing inorganic salts and their crystalline hydrates;
[0019] Optionally, the dispersant is polyethyleneimine, polyvinylidene fluoride, polyacrylic acid or polyvinyl alcohol, and its dosage is 0.025-3% of the mass of the raw material powder; preferably polyethyleneimine or polyacrylic acid, and its dosage is 0.1%.
[0020] Preferably, the Mg source, Al source and Ga source are MgO, Al2O3 and Ga2O3 powders with a purity greater than 99.9% and a particle size of 50 to 2000 nm. x Ga2O 4+1.5x The powder has a purity of more than 99.9%, a spherical shape, and a particle size of 100 to 1000 nm.
[0021] Optionally, the ball milling ball used in the ball milling step can be selected from one of corundum balls, silicon nitride balls, and zirconium oxide balls with a diameter of 2 to 10 mm. The ball-to-material ratio is (3 to 5):1; wet milling dispersion is adopted, and the dispersion solvent is one of small molecule organic solvents such as ethanol and acetone; the rotation speed is 100 to 350 r / min, and the ball milling time is not less than 6 hours.
[0022] Preferably, the ball milling balls described in step 1) are corundum balls with a diameter of 5 mm, the ball-to-material ratio is 4:1, the dispersion solvent is anhydrous ethanol, the rotation speed is 280 r / min, and the ball milling time is 24 h.
[0023] In the above scheme, the drying temperature in step 1) is 50-100° C., and the sieve used is larger than 50 mesh.
[0024] Preferably, the drying temperature in step 1) is 60-80° C., and the mesh size of the sieve is 100-200 meshes.
[0025] Optionally, the pressing molding in step 2) is dry molding or wet molding. Dry molding includes dry pressing and / or cold isostatic pressing; wet molding includes slip casting or gel casting.
[0026] In the above scheme, the sintering method of the dense material is pressureless sintering or a combination of pressure sintering and hot isostatic pressing, wherein before pressureless sintering, the powder is first subjected to cold isostatic pressing at a pressure of 150 to 300 MPa and a holding time of 5 to 20 minutes.
[0027] Furthermore, the sintering temperature of the pressureless sintering is 900-1500°C, the holding time is not less than 1h, and the atmosphere is one of vacuum, air, oxygen, hydrogen, nitrogen or argon; the hot pressing sintering temperature is 700-1400°C, the pressure is 10-90MPa, the holding time is not less than 0.2h, and the atmosphere is one of vacuum, hydrogen, nitrogen or argon; the spark plasma sintering temperature is 700-1400°C, the pressure is 10-90MPa, the holding time is not less than 0.2h, and the atmosphere is one of vacuum, hydrogen, nitrogen or argon; the hot isostatic pressing post-treatment temperature is 1200-1600°C, the pressure is 100-300MPa, the holding time is not less than 1h, and the pressurized medium is one of argon and nitrogen.
[0028] Furthermore, the pressure sintering adopts hot pressing sintering and spark plasma sintering processes, which includes a pressurization process without the need for an additional pressing step; preferably, when MgO, Al2O3, and Ga2O3 powders are used as raw materials, the hot pressing sintering process adopts a sintering temperature of 900-1300°C, a pressure of 40-90MPa, a holding time of 0.2-5h, and an atmosphere of vacuum or nitrogen; the spark plasma sintering process adopts a sintering temperature of 800-1300°C, a pressure of 50-90MPa, a holding time of 0.2-1h, and an atmosphere of nitrogen or argon; the pressureless sintering process adopts a sintering temperature of 1000-1500°C, a holding time of 4-10h, and an atmosphere of vacuum or air. The hot isostatic pressing post-treatment temperature is 1300-1500°C, the pressure is 100-300MPa, the insulation time is 4-8h, and the pressurizing medium is one of argon or nitrogen.
[0029] Preferably, MgAl x Ga2O 4+1.5xWhen powder is used as raw material, the sintering temperature used in the hot pressing sintering process is 900-1400℃, the pressure is 50-90MPa, the holding time is 1-8h, and the atmosphere is either vacuum or nitrogen; the sintering temperature used in the spark plasma sintering process is 900-1400℃, the pressure is 50-80MPa, the holding time is 0.5-1h, and the atmosphere is either nitrogen or argon; the sintering temperature used in the pressureless sintering process is 1000-1600℃, the holding time is 4-10h, and the atmosphere is either vacuum or air. The post-treatment temperature of hot isostatic pressing is 1300-1600℃, the pressure is 100-300MPa, the holding time is 4-10h, and the pressurized medium is either argon or nitrogen.
[0030] In the above scheme, the annealing temperature is 700-1200° C., and the holding time is longer than 2 hours.
[0031] Preferably, the annealing temperature is 800-1000° C., the holding time is 12-36 hours, and the atmosphere is oxygen.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The non-stoichiometric MgAl x Ga2O 4+1.5x There are a large number of cationic vacancies in the composition, which can promote the elimination of pores and avoid pore aggregation to a certain extent; the introduction of high molar mass Ga elements can effectively broaden the visible-infrared transmission range; in addition, the present invention further optimizes the wet grinding process and introduces a dispersant to refine the powder particle size, improve the powder uniformity and activity, promote the elimination of pores in the subsequent sintering process, and effectively solve the problem of light loss caused by pore scattering; the prepared non-stoichiometric MgAl x Ga2O 4+1.5x Transparent ceramics with stoichiometric Mg(Al x Ga 1- Compared with x)2O4-based transparent ceramics, the pore aggregation phenomenon has been greatly improved, the optical uniformity has been significantly improved, and it shows high transmittance in the visible-infrared band (0.5-6μm) and has good mechanical properties; at the same time, it can effectively solve the problems of narrow visible-infrared transmittance range of magnesium-aluminum spinel transparent ceramics, and the infrared cut-off edge has been widened by about 0.7-1.1μm.
[0034] (2) MgAl x Ga2O 4+1.5xThe composition and properties of transparent ceramics can be customized, and their optical and mechanical properties can be controlled by adjusting the x value; in particular, when x = 0.8-1.2, their mechanical properties are excellent, and the Vickers hardness can reach 12.6-13GPa; when x = 0.1-0.3, they have a wide infrared transmittance range, and their infrared cut-off wavelength is 7400-7500nm; the composition and properties of transparent ceramics can be designed and controlled as needed according to the service environment, effectively meeting the application requirements of optical and mechanical properties in the fields of transparent armor, infrared windows, and aircraft fairings.
[0035] (3) MgAl x Ga2O 4+1.5x The preparation method of transparent ceramics is simple to operate, low in cost, easy to obtain raw materials, and has stable and controllable conditions, making it suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 XRD diagrams of transparent ceramics prepared in Example 2 of the present invention and Comparative Examples 1 to 3;
[0037] Figure 2 The actual pictures are of the transparent ceramics prepared in Example 2 of the present invention and Comparative Examples 1 to 3;
[0038] Figure 3 Microstructure pictures of transparent ceramics prepared in Example 2 of the present invention and Comparative Examples 1 to 3;
[0039] Figure 4 Transmittance spectra of the transparent ceramics prepared in Example 2 of the present invention and Comparative Examples 1 to 3 in the ultraviolet-mid-infrared region. DETAILED DESCRIPTION
[0040] The following is a detailed and clear description of the technical solutions in the implementation cases of the present invention in conjunction with specific implementation cases. It should be clear that the implementation cases described here are only part of the present invention, not all. Any other implementation methods that can be thought of by those skilled in the art on the basis of the present invention without making creative efforts should be deemed to belong to the protection scope of the present invention.
[0041] Example 1
[0042] A transparent ceramic with high visible-infrared transmittance, the preparation method of which comprises the following steps:
[0043] 1) According to the chemical formula MgAl 0.88 Ga2O 5.32200 g of MgO, Al2O3 and Ga2O3 powders with a purity greater than 99.9% were weighed in a stoichiometric ratio of each element, and placed in a ball mill together with 800 g of corundum balls and 2 g of PEI. Anhydrous ethanol was used as a ball milling medium, and the mixture was ball milled at a speed of 180 r / min for 24 h to obtain a mixed powder slurry. The mixed slurry was placed in an oven for drying at a drying temperature of 70° C. for 24 h. After drying, the mixture was sieved with a 100-mesh sieve. The sieved powder was placed in a muffle furnace for calcination to remove organic matter. The calcination temperature was 600° C. and the insulation time was 12 h.
[0044] 2) The mixed powder is subjected to dry pressing at a pressure of 20 MPa and a holding time of 2 min, and then subjected to cold isostatic pressing at a pressure of 180 MPa and a holding time of 10 min to obtain a ceramic blank;
[0045] 3) The ceramic green body is placed in a high temperature furnace for pressureless sintering, the atmosphere is air, the sintering temperature is 1350°C, the holding time is 4h, the heating rate is 5°C / min, and the cooling method is natural cooling with the furnace; then the ceramic obtained by pressureless sintering is subjected to hot isostatic pressing treatment, the hot isostatic pressing temperature is 1600°C, the holding time is 5h, the pressure is 200MPa, and the pressurizing medium is nitrogen;
[0046] 4) The ceramic after hot isostatic pressing is annealed at 800°C for 12 hours in air atmosphere. After cooling to room temperature, the surface is polished to obtain the transparent ceramic. The specific process parameters and sample properties are shown in Table 1.
[0047] Example 2
[0048] A transparent ceramic with high visible-infrared transmittance, the preparation method of which comprises the following steps:
[0049] 1) Weigh MgAl with a purity greater than 99.9% 0.88 Ga2O 5.32 A total of 200 g of powder was placed in a ball mill with 750 g of corundum balls and 2 g of PEI. Anhydrous ethanol was used as the ball milling medium. The powder was milled at a speed of 200 r / min for 36 hours to obtain a powder slurry. The powder slurry was placed in an oven for drying at a drying temperature of 70°C for 24 hours. After drying, the powder was sieved with a 200-mesh sieve. The sieved powder was placed in a muffle furnace for calcination to remove organic matter. The calcination temperature was 600°C and the insulation time was 12 hours.
[0050] 2) The ceramic powder is dry pressed at a pressure of 25 MPa and a holding time of 2 min, and then cold isostatically pressed at a pressure of 180 MPa and a holding time of 10 min to obtain a ceramic green body, and the ceramic green body is calcined in a muffle furnace to remove organic matter at a calcination temperature of 600° C. and a holding time of 12 h to obtain a ceramic green body;
[0051] 3) placing the ceramic green body in a high temperature furnace for pressureless sintering, the atmosphere is air, the sintering temperature is 1400°C, the holding time is 6 hours, the heating rate is 10°C / min, and the cooling method is natural cooling with the furnace; then the ceramic obtained by pressureless sintering is subjected to hot isostatic pressing, the hot isostatic pressing temperature is 1600°C, the holding time is 5 hours, the pressure is 250MPa, and the pressurizing medium is nitrogen;
[0052] 4) The ceramic after hot isostatic pressing is annealed at a temperature of 850° C. for 12 h in an air atmosphere. After cooling to room temperature, the surface is polished to obtain the transparent ceramic. The specific process parameters and sample properties are shown in Table 1.
[0053] Example 3
[0054] A transparent ceramic with high visible-infrared transmittance, the preparation method of which comprises the following steps:
[0055] 1) According to the chemical formula MgAl 0.02 Ga2O 4.03 200 g of MgO, Al2O3 and Ga2O3 powders with a purity greater than 99.9% are weighed in a stoichiometric ratio of each element, and placed in a ball mill together with 800 g of corundum balls and 2 g of PEI. Anhydrous ethanol is used as a ball milling medium, and the mixture is ball milled at a speed of 200 r / min for 24 h to obtain a mixed powder slurry; the mixed slurry is placed in an oven for drying at a drying temperature of 70°C for 24 h, and after drying, the mixture is sieved with a 100-mesh sieve to obtain a uniformly mixed powder, and the powder is placed in a muffle furnace for calcination to remove organic matter, and the calcination temperature is 600°C for a holding time of 12 h;
[0056] 2) 40-50 g of the powder was placed in a hot pressing mold for hot pressing sintering, the sintering temperature was 1000° C., the pressure was 60 MPa, the holding time was 2 h, and the atmosphere was nitrogen; the ceramic obtained by hot pressing sintering was subjected to hot isostatic pressing, the hot isostatic pressing temperature was 1400° C., the holding time was 5 h, the pressure was 200 MPa, and the pressurizing medium was nitrogen;
[0057] 3) The ceramic after hot isostatic pressing is annealed at a temperature of 750° C. for 36 h in an air atmosphere. After cooling to room temperature, the surface is polished to obtain the transparent ceramic. The specific process parameters and sample properties are shown in Table 1.
[0058] Example 4
[0059] A transparent ceramic with high visible-infrared transmittance, the preparation method of which comprises the following steps:
[0060] 1) Weigh MgAl with a purity greater than 99.9% 0.26 Ga2O 4.39 A total of 200 g of powder was placed in a ball mill with 750 g of corundum balls and 2 g of PEI. Anhydrous ethanol was used as the ball milling medium. The powder was milled at a speed of 250 r / min for 18 h to obtain a powder slurry. The powder slurry was placed in an oven for drying at a temperature of 70 ° C for 24 h. After drying, the powder was sieved with a 200-mesh sieve. The powder was then placed in a muffle furnace for calcination to remove organic matter. The calcination temperature was 600 ° C and the insulation time was 12 h.
[0061] 2) 50-60 g of powder was placed in a mold for spark plasma sintering at a sintering temperature of 1200° C., a pressure of 50 MPa, a holding time of 0.4 h, and an argon atmosphere; the ceramic obtained by the spark plasma was subjected to hot isostatic pressing at a hot isostatic pressing temperature of 1500° C., a holding time of 5 h, a pressure of 250 MPa, and a pressurizing medium of nitrogen;
[0062] 3) The ceramic after hot isostatic pressing is annealed at 900°C for 24 hours in air atmosphere. After cooling to room temperature, the surface is polished to obtain the transparent ceramic. The specific process parameters and sample properties are shown in Table 1.
[0063] Example 5
[0064] A transparent ceramic with high visible-infrared transmittance, the preparation method of which comprises the following steps:
[0065] 1) According to the chemical formula MgAl 0.58 Ga2O 4.87Weigh 200g of Mg(OH)2, Al2O3, and Ga2O3 powders with a purity greater than 99.9% in the stoichiometric ratio of each element, place them in a ball mill together with 800g of corundum balls, use anhydrous ethanol as the ball milling medium, and ball mill them at a speed of 200r / min for 24h on the ball mill to obtain a mixed powder slurry; place the mixed slurry in an oven to dry at a drying temperature of 70℃ for 24h, and sieve it with a 100-mesh screen after drying to obtain a uniformly mixed powder; place the mixed powder in a muffle furnace and calcine it for 3h at a calcination temperature of 1100℃ and a heating rate of 10℃ / min. After the calcined powder is cooled to room temperature, place it in a ball mill together with 700g of corundum balls and 2g of PEI. Using anhydrous ethanol as a ball milling medium, ball milling is performed on a ball mill at a speed of 280 r / min for 24 hours to obtain a ceramic powder slurry; the powder slurry is placed in an oven for drying at a drying temperature of 70°C for a drying time of 24 hours, and after drying, the powder is sieved with a 200-mesh sieve to obtain a ceramic powder, and the sieved powder is placed in a muffle furnace for calcination to remove organic matter, the calcination temperature is 600°C, and the insulation time is 12 hours;
[0066] 2) 50-60 g of powder was placed in a mold for spark plasma sintering at a sintering temperature of 1300° C., a pressure of 60 MPa, a holding time of 0.4 h, and an argon atmosphere; the ceramic obtained by the spark plasma was subjected to hot isostatic pressing at a hot isostatic pressing temperature of 1500° C., a holding time of 5 h, a pressure of 250 MPa, and a pressurizing medium of nitrogen;
[0067] 3) The ceramic after hot isostatic pressing is annealed at 925°C for 24 hours in air atmosphere. After cooling to room temperature, the surface is polished to obtain the transparent ceramic. The specific process parameters and sample properties are shown in Table 1.
[0068] Example 6
[0069] A transparent ceramic with high visible-infrared transmittance, the preparation method of which comprises the following steps:
[0070] 1) Weigh MgAl with a purity greater than 99.9% 1.16 Ga2O 6.9 A total of 200 g of powder was placed in a ball mill with 750 g of corundum balls and 2 g of PEI. Anhydrous ethanol was used as the ball milling medium. The powder was milled at a speed of 260 r / min for 24 h to obtain a powder slurry. The powder slurry was placed in an oven for drying at a drying temperature of 70°C for 24 h. After drying, the powder was sieved with a 200-mesh sieve. The sieved powder was placed in a muffle furnace for calcination to remove organic matter. The calcination temperature was 600°C and the insulation time was 12 h.
[0071] 2) Weigh 50-60g of powder and place it in a mold for hot pressing sintering. The sintering temperature is 1300°C, the pressure is 90MPa, the holding time is 5h, and the atmosphere is nitrogen;
[0072] 3) The hot-pressed sintered ceramic was annealed at 900°C for 36 hours in an air atmosphere. After cooling to room temperature, the surface was polished to obtain the transparent ceramic. The specific process parameters and sample properties are shown in Table 1.
[0073] Comparative Example 1
[0074] A transparent ceramic, the preparation method of which is substantially the same as that of Example 2, except that:
[0075] In step 1), a stoichiometric MgAl with a purity greater than 99.9% is used. 0.51 Ga 0.49 O4 powder;
[0076] Comparative Example 2
[0077] A transparent ceramic, the preparation method of which is substantially the same as that of Example 2, except that:
[0078] In step 1), non-stoichiometric MgAl with a purity greater than 99.9% is used. 2.88 O 5.32 powder.
[0079] Comparative Example 3
[0080] The preparation method of a transparent ceramic is substantially the same as that of Example 2, except that no PEI dispersant is added.
[0081] Figure 1 The XRD images of the transparent ceramics prepared in Example 2 and Comparative Examples 1 to 3 show that, compared with Comparative Examples 1 and 2, the product obtained in Example 2 has obvious deviation in the same diffraction peak position.
[0082] After double-sided polishing, the ceramic obtained in Comparative Example 1 has white spots visible to the naked eye. The SEM image shows that these white spots are formed by the aggregation of a large number of pores. 0.88 Ga2O 5.32 There are no white spots visible to the naked eye. This is due to the non-stoichiometric MgAl 0.88 Ga2O 5.32 The presence of a large number of cation vacancies will hinder the aggregation of pores and show a more uniform microstructure. 0.88 Ga2O 5.32 In the visible-infrared region, it shows a higher 0.51 Ga0.49 O4 has higher transmittance.
[0083] Although Comparative Example 2 also has a relatively high optical transmittance, its range in the visible-infrared band is narrower than that of Example 2 by about 0.5 μm; Figure 2 Although there are no white spots visible to the naked eye, there are still a few pores inside the crystal (see Figure 4 ).
[0084] Although the product obtained in Comparative Example 3 has no white spots visible to the naked eye, its corresponding optical transmittance is relatively low, and there are also fewer pores inside the crystal.
[0085] Table 1 Specific process parameters and sample properties of transparent ceramic samples prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 3
[0086]
[0087]
[0088]
[0089] The preparation methods provided in Examples 1 to 6 successfully prepared MgAl x Ga2O 4+1.5x Transparent ceramics, and transparent ceramics with higher optical transmittance are obtained, which is due to its uniform microstructure. Compared with comparative examples 1 to 3, the composition involved in this patent has a wider infrared cutoff edge while maintaining higher optical transmittance and uniformity. The average grain size of the prepared transparent ceramics is less than (size is 5 to 50 μm), the transparent ceramics reach a theoretical sintering density of more than 99.5%, the transmittance range is 250 to 7500 nm, the elastic modulus is 250 to 300 MPa, and the hardness is 12 to 13 GPa. Especially when x takes a value of about 0.88, the optical transmittance at 2 to 5 μm is more than 80%, the hardness is 12.8 GP, and the Young's modulus is 275 GPa, taking into account excellent optical transmittance and good mechanical properties. The transparent ceramics can meet the needs of transparent armor, infrared windows, aircraft fairings and protective windows.
[0090] The MgAl x Ga2O 4+1.5x The method for preparing transparent ceramics can flexibly combine the powder processing process and the sintering process mentioned in the above method. The process parameters of each step can not only be reasonably selected within the condition parameter range provided in the above method, but can also be further optimized and screened by professional and technical personnel within the framework of the above process system. These embodiments are for illustrative purposes only and do not constitute a limitation on the scope of the present invention.
[0091] The specification of the present invention elaborates on many specific details. However, it must be clear that these specific embodiments are not the only implementation methods of the present invention. In fact, even without these detailed details, the embodiments of the present invention can still be effectively implemented. The above embodiments only represent the preferred embodiments of the process system of the present invention and do not constitute a limitation on other forms of the present invention. Any technician with professional knowledge in the fields of inorganic non-metallic materials, ceramics, glass, etc. can make appropriate changes based on the disclosed technical content, and these changes should be regarded as equivalent embodiments. As long as these changes do not deviate from the core technical solution of the present invention, that is, simple modifications, equivalent changes and modifications to the embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A transparent ceramic with high visible-infrared transmittance, characterized in that: Its general chemical formula is MgAl x Ga2O 4+1.5x , the value range of x is 0<x≤1.
5.
2. The transparent ceramic according to claim 1, characterized in that: The average grain size of the transparent ceramic is not higher than 50 μm, the size distribution is uniform and the extreme difference is not more than 10 μm, and there is no local pore aggregation.
3. The transparent ceramic according to claim 1, characterized in that: The optical transmittance range of the transparent ceramic is 250-7500nm; the highest transmittance in the visible light band of 400-800nm is ≥82%, and the highest transmittance in the infrared band of 2-5μm is ≥83%.
4. The method for preparing transparent ceramics with high visible-infrared transmittance according to claims 1 to 3, characterized in that: The following steps are involved: 1) Single-phase MgAl x Ga2O 4+1.5x Powder or MgAl x Ga2O 4+1.5x Weighing a mixed powder of Mg, Al source and Ga source in a stoichiometric ratio as a raw material powder, mixing it with a ball milling medium and a dispersant, and then ball milling, drying, calcining, and sieving to obtain a target powder; 2) pressing the powder obtained in step 1) into a shape and sintering to obtain a ceramic sintered body with a density greater than 99%; 3) annealing the obtained ceramic sintered body in an oxidizing atmosphere, cooling, and polishing to obtain the transparent ceramic with high visible-infrared transmittance.
5. The preparation method according to claim 4, characterized in that: In the ball milling step of step 1), the ball to material ratio is (3-5):1, the rotation speed is 100-350r / min, and the ball milling time is not less than 6h.
6. The preparation method according to claim 4, characterized in that: In step 1), the dispersant is polyethyleneimine, polyvinylidene fluoride, polyacrylic acid or polyvinyl alcohol.
7. The preparation method according to claim 4, characterized in that: Step 2) The dense sintering adopts a pressureless sintering or a pressure sintering process, wherein before the pressureless sintering, the powder is first pressed into shape and then subjected to cold isostatic pressing; the pressure sintering adopts a hot pressing sintering or spark plasma sintering process without the need for an additional molding step.
8. According to the preparation method of claim 7, the sintering temperature is 900-1500°C, the holding time is more than 1 hour, and the atmosphere is one of vacuum, air, oxygen, hydrogen, nitrogen, and argon; the hot pressing sintering temperature is 700-1400°C, the pressure is 10-90MPa, the holding time is more than 0.2h, and the atmosphere is one of vacuum, hydrogen, nitrogen, and argon; the spark plasma sintering temperature is 700-1400°C, the pressure is 10-90MPa, the holding time is more than 0.2h, and the atmosphere is one of vacuum, hydrogen, nitrogen, and argon.
9. The preparation method according to claim 7, characterized in that: After pressureless or pressure sintering, hot isostatic pressing is performed; the temperature of hot isostatic pressing post-treatment is 1200-1600°C, the pressure is 100-300MPa, the insulation time is more than 1h, and the pressurizing medium is one of argon and nitrogen.
10. The preparation method according to claim 4, characterized in that: The annealing temperature in step 3) is 700-1200° C., and the holding time is longer than 2 hours.
Citation Information
Patent Citations
Visible-infrared transparent ceramic and preparation method thereof
CN114773049A
Spinel type high-entropy transparent ceramic as well as preparation method and application thereof
CN117986004A
Zn-Ti OXIDE SPUTTERING TARGET AND METHOD FOR PRODUCING THE SAME
JP2018087361A
Colored spinel optoceramics
US20110143912A1